Europe and the rescaling of domestic territorial governance in Ireland. Issue 2 (14th March 2020) - Callanan, Mark
ABSTRACT: The European Union (EU) has had a considerable impact on territorial governance in Ireland, including both significant financial and regulatory effects and some examples of domestic institution-building. This article addresses some of the effects of these 'top-down' pressures, but also 'bottom-up' processes that have manifested themselves over time through the mobilization of actors at both regional and local levels. In part differing effects can be explained by the range of Europeanization mechanisms used in distinct areas, from 'hard law' regulatory instruments to weaker framing mechanisms. The experience of Irish territorial governance suggests that Europeanization pressures to adapt (both top-down and bottom-up) are filtered through domestic traditions and norms. In the Irish case, the European opportunity structure can be said to have had both decentralizing and centralizing effects in terms of local government. It has also had very mild regionalization effects, but these are now entwined with domestic pressures.